Corporate practices and health: a framework and mechanisms - Joana Madureira Lima; Sandro Galea (BMC, 2018)
Abstract Background The Global Burden of Disease estimates that approximately a third of deaths worldwide are attributable to behavioural risk factors that, at their core, have the consumption of unhealthful products and exposures produced by profit driven commercial entities. We use Steven Lukes' three-dimensional view of power to guide the study of the practices deployed by commercial interests to foster the consumption of these commodities. Additionally, we propose a framework to systematically study corporations and other commercial interests as a distal, structural, societal factor that causes disease and injury. Our framework offers a systematic approach to mapping corporate activity, allowing us to anticipate and prevent actions that may have a deleterious effect on population health. Conclusion Our framework may be used by, and can have utility for, public health practitioners, researchers, students, activists and other members of civil society, policy makers and public servants in charge of policy implementation. It can also be useful to corporations who are interested in identifying key actions they can take towards improving population health.